Double phase logistic equations with superdiffusive reaction. (April 2023) - Gasiński, Leszek; Papageorgiou, Nikolaos S.
Abstract: We consider double phase problems with unbalanced and balanced growth and logistic reaction of the superdiffusive type. We prove existence and multiplicity results and discuss how the two cases differ.